Tooth size discrepancies in Class II division 1 and Class III malocclusion requiring surgical–orthodontic or orthodontic treatment. (June 2014) - McSwiney, Timothy P; Millett, Declan T; McIntyre, Grant T; Barry, Mark K; Cronin, Michael S
Abstract : Objective: To compare mean anterior (AR) and mean overall (OR) tooth size ratios, prevalence of clinically significant tooth size discrepancies (TSDs) and correlation between AR and OR in subjects with Class II division 1 and Class III malocclusion treated by surgical–orthodontic or orthodontic means.Design: Retrospective, cross-sectional.Setting: State-funded and private clinics.Participants: From pre-treatment cohorts of 770 surgical and 610 non-surgical subjects, Class II division 1 and Class III malocclusion groups were identified with 60 surgical and 60 non-surgical subjects, comprising 30 males and 30 females, in each.Methods: AR and OR were calculated by landmarking digital models. Differences in AR and OR and their relationship were analysed using two-way analysis of variance (ANOVA) and a correlation coefficient, respectively. The proportions of the surgical and non-surgical groups with a TSD were assessed using logistic regression. Intra-examiner reproducibility involved re-landmarking 30 randomly selected image sets and differences in ARs and ORs were compared using a paired t -test. Random error was assessed using the intraclass correlation coefficient (ICC). Analyses were performed using SAS (SAS Institute Inc., Cary, NC, USA) at the 5% level of significance.Results: There were no statistically significant differences associated with the measurement of either the mean AR ( P = 0·913) or the mean OR ( P = 0·874). ICC values were very high (AR = 0·95; OR = 0·90). Differences existed between both Class II and Class III surgical (AR: P <0·001; OR: P <0·001) and non-surgical groups (AR: P = 0·012; OR: P = 0·003). The AR and OR relationship was strong (correlation coefficient = 0·72). The highest percentage of clinically significant TSDs was seen in the AR of both Class II and Class III surgical groups (23·3%).Conclusions: In the cohort examined: AR and OR differed significantly for malocclusion groups. The prevalence of clinically significant TSDs did not differ significantly between surgical and non-surgical groups although the highest percentage of clinically significant TSDs was recorded for AR in Class II and Class III surgical cases. AR and OR were closely related.